Pilot study of an integrated model of sleep support for children: a before and after evaluation. Issue 1 (10th November 2019) - Elphick, Heather E; Lawson, Candi; Ives, Ann; Siddall, Sue; Kingshott, Ruth N; Reynolds, Janine; Dawson, Victoria; Hall, Lorraine
Abstract : Objective: Despite the success of behavioural sleep support interventions in the third sector, sleep support is not universally available for families in the UK. The aim of the study was to provide evidence of efficacy and to propose a delivery model for integrated sleep support for families of vulnerable children. Design and setting: A sleep support intervention was carried out in Sheffield Local Authority evaluated using a preintervention and postintervention study design by Sheffield Children's National Health Service (NHS) Trust. Participants: Fifty-six children aged 6–16 years with significant sleep problems were recruited; 39 completed the intervention and evaluation. Interventions: Basic sleep education and an individualised programme was delivered by a sleep practitioner. Follow-on telephone support was provided to empower the parent (and/or young person) to carry out the sleep programme at home. An integrated NHS and Local Authority delivery model was designed and implemented. Results: Parents' ratings of their child's ability to self-settle improved from 1.1/10 to 6.4/10 (p<0.05). Mean Warwick-Edinburgh Mental Well-being Scale scores improved significantly for parents/carers (MD 5.16, 95%CIs 2.62 to 7.69, p<0.05). Children who completed the intervention gained on average an extra 2.4 hours sleep a night. There was reduction in healthcare utilisation, illnesses and medication use. Conclusions: The behavioural approach to sleep support for these vulnerable groups of children is highly effective. Follow-on individual support to empower parents is key to achieving success. Sleep support can be implemented in NHS and Local Authority services by integration into the existing workforce using a cross-agency model.